ANTIBIOTICS RESISTANCE RISK ASSOCIATED WITH ANTIBIOTIC OVERUSE - Rabat, Hawraa Hadi Ali; Mashed, Fatima Sadiq Abd Al Hussein; Hassoun, Wuroud Saad Muhammed; Tamig, Teba Adnan saber; Abbas, Sabreen sahib Mohsin (Journal of Medical Genetics and Clinical Biology, 2024)
Antimicrobial resistance is a global public health challenge, which has accelerated by the overuse of antibiotics worldwide. Increased antimicrobial resistance is the cause of severe infections, complications, longer hospital stays and increased mortality. Overprescribing of antibiotics is associated with an increased risk of adverse effects, more frequent re-attendance and increased medicalization of self-limiting conditions. Antibiotic overprescribing is a particular problem in primary care, where bacteria cause most infections. About 90% of all antibiotic prescriptions are issued by general practitioners, and respiratory tract infections are the leading reason for prescribing. Multifaceted interventions to reduce overuse of antibiotics have been found to be effective and better than single initiatives. Interventions should encompass the enforcement of the policy of prohibiting the over-thecounter sale of antibiotics, the use of antimicrobial stewardship programmes, the active participation of clinicians in audits, the utilization of valid rapid point-of- care tests, the promotion of delayed antibiotic prescribing strategies, the enhancement of communication skills with patients with the aid of information brochures and the performance of more pragmatic studies in primary care with outcomes that are of clinicians’ interest, such as complications and clinical outcomes.